Inspeksi Visual Asam Asetat (IVA) untuk Deteksi Dini Lesi Prakanker Serviks - Sapto Wiyono; T. Mirza Iskandar; Suprijono Suprijono (MEDIA MEDIKA INDONESIANA, 2008)
Visual acetic acid inspection (IVA) for early cervix pre cancer lesion detectionBackground: In 1985 WHO and had recommended an alternative approach, the down staging concept of cervical malignancy with visual inspection with acetic acid (VIA) for developing countries. Displastic cervical epithelial cells will make an acethowhite appearance with VIA. It is important to know the sensitivity and specificity of VIA for early detection of cervical precancer lesion.Methods: A hundred and twenty subjects who fullfilled inclution criteria had Pap test, VIA and four quadrant biopsy. Fortyfive subjects came from Gynecology and fertility clinic at Dr. Kariadi hospital and seventy five subjects came from Indonesian Cancer Foundation Semarang. From all of these examination the sensitivity, specificity, positive predictive value and negative predictive value were calculated by 2x2 tabel. Biopsy result was considered as gold standard.Results: Based on biopsy result there were 32 cases (26.7%) with normal finding, 31 cases (25.81%) with chronic cervicitis, 50 cases (41.6%) with chronic cervicitis with mild dysplasia, 3 cases (2.5%) with chronic cervicitis and moderate dysplasia, 2 cases (1.7%) with non specific inflammation, 2 cases (1.7%) with chronic cervicitis and mild dysplasia, 1 cases (0.8%) with malignancy. The sensitivity of Pap test was 55%, specificity 90%, PPV 84% and NPV 69% whether VIA had sensitivity 84%, specificity 89%, PPV87% and NPV 86%.Conclusions: Visual inspection with acetic acid has high sensitivity for early detection of cervical precancer lesion.Keywords: VIA, acetowhite, early detection, cervical precancer lesion.ABSTRAKLatar belakang: Tahun 1985 WHO merekomendasikan suatu pendekatan alternatif bagi negara yang sedang berkembang dengan konsep down staging terhadap kanker serviks dengan pemeriksaan IVA. Epitel serviks yang mengalami displasia akan memberikan gambaran acethowhile dengan pemeriksaan IVA. Untuk itu perlu diketahui seberapa besar sensitivitas dan spesifisitas dari pemeriksaan VIA dalam mendeteksi dini lesi prakanker serviks.Metode: Seratus dua puluh peserta penelitian, 45 berasal dari poliklinik ginekologi dan FER RSUP Dr. Kariadi dan 75 berasal dari YKI Cabang Semarang yang memenuhi kriteria penerimaan sampel dilakukan pemeriksaan tes Pap, IVA dan biopsi empat kuadran. Terhadap hasil pemeriksaan ini dilakukan perhitungan sensitivitas, spesifisitas, nilai duga positif maupun nilai duga negatifHasil: Berdasarkan hasil pemeriksaan biopsi didapatkan 32 subyek (26,7%) dengan hasil normal, 31 (25,8%) dengan servisitis kronis, 50 (41,6%) dengan servisitis kronis dengan displasia ringan, 3 (2,5%) servisitis kronis dengan displasia sedang, 2 (1,7%) dengan radang tidak spesifik dengan displasia ringan, 2 (1,7%) dengan radang tidak spesifik dan 1 (0,8%) dengan keganasan serviks. Sensitivitas untuk tes Pap 55%, spesifisitas 90%, nilai duga positif 84%, nilai duga negatif 69%, sedang sensitivitaspemeriksaan IVA 84%, spesifisitas 89%, nilai duga positif 87% dan nilai duga negatif 86%.Simpulan: Pemeriksaan IVA mempunyai sensitivitas yang tinggi untuk deteksi dini lesi prakanker serviks.